Sri Lanka Workforce Development : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2015)
Sustained economic growth and structural change has been a feature of the Sri Lankan economy over the past decade, despite armed internal conflict and the global financial crisis. This has transformed the skills requirements of the workforce. The country is following an ambitious development plan, published under the title ‘Mahinda Chintana,'aiming to become a regional hub in strategic economic areas and to transform itself into an efficiency driven middle income economy. As a result, the demand for skills is likely to accelerate. Unfortunately, despite high achievements in general education, major skills gaps and mismatches in the labor market remain that constrain firm and worker productivity. The government of Sri Lanka recognizes the critical importance of developing a skilled labor force for achieving the country's development goals, and it is committed to building a high quality, market demand driven, and responsive workforce development (WfD) system. The strategic directions for WfD are outlined in both ‘Mahinda Chintana' and the National Human Resources and Employment Policy. The WfD sector wide strategy is being developed by the Ministry of Finance and Planning and other relevant line ministries to operationalize these strategic directions. The SABER WfD diagnostic tool presents a great opportunity to enrich the policy dialogue on WfD in Sri Lanka, helping the government of Sri Lanka identify key bottlenecks and set priorities in the WfD process.